Sistem Pendukung Keputusan Pengoptimalan Pembagian Tugas dengan Metode Assignment Berbasis Web - Julianto Lemantara; Tantri Windarti (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
In dividing assignment, manager is not recommended to make decision with only intuition and experience, but must be based on facts. The problem is the fact-based decisions will be long or difficult to do with conventional ways. Therefore, Decision Support Systems (DSS) is needed. In DSS, providing advice should be more than one option so that manager can choose the bestoption. However, commercial applications for assignment cases in operation research can only provide one optimal solution. Besides, commercial applications cannot handle assessment process that has specific criteria, such as Microsoft Excel and WinQSB. The theory used in thisapplication was assignment method. The study implementation used waterfall model in System Development Life Cycle method. The study results show that the application can produce optimal solutions more than one option if possible so that it repairs the lack of commercial applications in operation research. Thisapplication can also give solution for any assignments accurately and comprehensively because it can handle assignment assessment that has spesific criteria.